Considering Marijuana Legalization Insights for Vermont and Other Jurisdictions - Caulkins, Jonathan P. (RAND Corporation, 2015)
Marijuana legalization is a controversial and multifaceted issue that is now the subject of serious debate. In May 2014, Vermont Governor Peter Shumlin signed a bill requiring the Secretary of Administration to produce a report about various consequences of legalizing marijuana. This resulting report provides a foundation for thinking about the various consequences of different policy options while being explicit about the uncertainties involved.